The fallacy of the “intentional fallacy”: the intended sense of William Shakespeare’s The Merchant of Venice - Cabral, Tiago (Revista PHILIA | Filosofia, Literatura & Arte, 2025)
Members of New Criticism, an American school of criticism that predominated in the decades of 1940 and 1950, coined the intentional and the affective fallacies, which essentially dictated the intentions of an author are irrelevant to the meaning of a literary text. To refute this principle, I discuss William’ Shakespeare’s comedy The Merchant of Venice. In the play, Shylock is the antagonist, the comic villain, which is a key feature of the intended meaning of the play. In this article, I purport to show how this anti-aesthetic principle from New Criticism contributes little for literary criticism.